2015
DOI: 10.21071/az.v64i245.371
|View full text |Cite
|
Sign up to set email alerts
|

Polimorfismos de los genes CAPN1, CAST, DES, PRKAG3 Y RYR1 asociados a la capacidad de retención de agua en crudo y cocinado en carne de bovino en cruces Bos indicus y Bos taurus en Colombia

Abstract: La capacidad de retención de agua (CRA) es uno de los parámetros de calidad de la carne más importante, dado que posee asociación con la percepción de jugosidad y la pérdida de peso de la pieza cárnica durante procedimientos como la maduración, la cocción y otro tipo de procesamiento tecnológico. La CRA en crudo y cocinado (CRAr y CRAc respectivamente) fue evaluada en 164 machos castrados cruzados, en los cuales se realizó la genotipificación de 23 regiones genómicas de los genes CAPN1, CAST, DES, PRKAG3 y RYR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
0
4
0
2
Order By: Relevance
“…To account for effects of cooking loss on tenderness unrelated to muscle proteolysis ( Kołczak et al, 2007 ; Bouhrara et al, 2011 , 2012 ), cooking loss was included as a covariate in the association analysis. Leal-Gutiérrez et al (2015) found a highly significant association between the Cast5 marker and water holding capacity in raw meat. However, Cast5 had no significant effect on cooking loss.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…To account for effects of cooking loss on tenderness unrelated to muscle proteolysis ( Kołczak et al, 2007 ; Bouhrara et al, 2011 , 2012 ), cooking loss was included as a covariate in the association analysis. Leal-Gutiérrez et al (2015) found a highly significant association between the Cast5 marker and water holding capacity in raw meat. However, Cast5 had no significant effect on cooking loss.…”
Section: Discussionmentioning
confidence: 88%
“… Curi et al (2009) showed that Cast5 was significantly associated with shear force (SF) and the myofibrillar fragmentation index, reporting the T allele as the favorable one. An association between Cast5 and water holding capacity in raw meat in a crossbred Bos indicus–Bos taurus population was found by Leal-Gutiérrez et al (2015) . McClure et al (2012) assessed the association of 28 SNPs in calpastatin with WBSF of Longissimus dorsi steaks of 3360 animals.…”
Section: Discussionmentioning
confidence: 98%
“…The drip loss can be considered of high economic and productive importance due to the weight loss of the meat that takes place during storage, which affects meat quality (Leal-Gutiérrez et al, 2015). In breast meat, drip loss varied between 1.25% and 1.74% (Table 3), without significant differences among treatments (P > 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…The burgers with ammonium hydroxide in solutions of 0.5% and 1.0% w / v yielded the highest values p <0.05) of CRA, in contrast the formulations with 1.5% and the control presented the lowest values during the days of storage at 4 °C. The CRA is one of the most important quality parameters of the meat, it is directly linked to the perception of juiciness and weight loss of the product during later stages such as cooking and other technological processes [27]; when the concentration of HA was increased to 1.5%, the burgers showed a reduction in the CRA, this can be explained by the influence of the pH that determines the number of reactive groups of the proteins and their capacity to bind water [28].…”
Section: Resultsmentioning
confidence: 99%